Feline lymphoma of the nervous system. Immunophenotype and anatomical patterns in 24 cases - Mandara, Maria Teresa; Domini, Alessia; Giglia, Giuseppe (Frontiers in Veterinary Science, 2022)
This study aimed to describe the specific localization and anatomical pattern of 24 feline lymphomas of the nervous system for which the immunophenotype was identified by immunohistochemistry investigations to support the potential specific correlation between subtypes and anatomical patterns. In total 10 tumors affected the spinal cord, eight the brain, four the peripheral nerves, one involved both the brain and the spinal cord, and one simultaneously the brain and the optic nerves. Twenty two tumors were primary lymphomas. The affected animals were 8 years of mean age. Tumors developed as an extra-axial mass (11 cases), intra-axial mass (six cases), leptomeningeal lymphomatosis (three cases), and neurolymphomatosis (five cases). One of them expressed both leptomeningeal lymphomatosis and neurolymphomatosis patterns. Two intra-axial brain lymphomas showed an angiotropic pattern. The optic chiasm was the most involved site for neurolymphomatosis. Immunolabeling was performed using anti-CD3, CD20, CD79a, PAX5, MUM-1, CD56, and anti-CD44 antibodies. In total, 12 tumors consisted of B cell lymphomas, and six of T cell lymphomas, two cases were double-reactive lymphomas while two cases consisted of non-B non-T lymphomas. B cell lymphoma affected animals of 6.4 years of mean age, while the T cell lymphoma affected older animals (mean age of 11.1 years). Extra-axial tumors mainly consisted of B cell lymphomas (8/11). Neurolymphomatosis expressed different immunophenotypes, and the B cell phenotype was the most prevalent in the optic chiasm. Two leptomeningeal lymphomatoses expressed T cell immunophenotype. For the first time, plasmacytoid differentiation was found for angiotropic lymphoma and neurolymphomatosis. All the cases, except one, were CD56-negative. CD44-expression confirmed a common malignant potential for all the anatomical patterns of the nervous system lymphoma in cats. Immunophenotype of feline lymphoma of the nervous system and its potential association with specific anatomical patterns should be strongly required in the diagnostic workup and clinical approach to this tumor especially when its primary origin is confirmed.